PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN EKOWISATA MANGROVE DI DESA BOKOR KABUPATEN KEPULAUAN MERANTI - Said Jamaluddin Syaputra; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is motivated by the inadequate use of ecotourism development in Bokor Village. Community empowerment in the development of mangrove ecotourism has not been maximized due to the lack of public awareness of the potential of ecotourism in Bokor Village which should be better utilized and different from before, the threat of neglected potential that should be able to be felt. the benefits of the Bokor Village community if the appropriate empowerment program is not carried out immediately. This is what makes researchers interested in knowing how the stages of community empowerment that have taken place in the village of Bokor are carried out by the Tourism, Youth and Sports Office of the Meranti Islands Regency as an empower who has conducted nature tour guide training, homestay development training, etc. Also synergizing with the Bokor Village government in accelerating the development of mangrove ecotourism in Bokor Village and from among the community is the Bathin Galang tourism awareness group which actively participates in community empowerment stages in the development of mangrove ecotourism in Bokor Village. In this study using qualitative methods using interview techniques, documentation,observation. Researchers use the theory from Ambar Teguh Sulistiyani regarding the stages of empowerment. Keywords: Society Empowerment, Development, Ecotourism